Hybrid nanowire-hyperbolic metamaterial based broadband absorber for the visible and near-infrared regions - Buranasiri, Prathan; Plaipichit, Suwan; Puttharugsa, Chokchai; Wicharn, Surawut (My University, 2021)
In this work, spectral absorbance of hybrid nanowire-hyperbolic metamaterial was investigated numerically by using transfer-matrix method. The hybrid nanowire-hyperbolic metamaterial is consisted of two-dimensional periodically arranged arrays of subwavelength-sized hybrid nanowires (with circular cross-section) embedded in silicon dioxide host matrix. Each hybrid nanowire is made by core-shell structure used silicon as a core and gold as a shell. The hybrid nanowire-hyperbolic metamaterial is used as a top layer of a broadband absorber. The top layer is over on a planar silicon dioxide layer, which is backed by a nano-sized layer of gold as a perfect reflector for guaranteeing high absorbance. When electromagnetic waves in the range of 400–1600 nm wavelength are obliquely incident on the top hybrid nanowire-hyperbolic metamaterial surface, the absorption spectra of the designed absorber structure are analyzed for different incident angles, and radii of hybrid nanowire components or fill-factor of the hyperbolic metamaterial layer. The multiple absorption peaks, which are continuously generated from multiple longitudinal and transverse surface plasmon modes and are supported by the hybrid nanowires, are observed directly. The absorption feature can be also tuned by various operational conditions. The proposed structure is made by in-complex nano-fabricating techniques comparing with the another and it provides acceptable broadband absorptivity.
Keywords: Hybrid-nanowire hyperbolic metamaterial; Optical absorber; Transfer matrix method